What do Flaubert, Dostoevsky and Machado de Assis have in common with neurology? - Bruno Kusznir Vitturi; Wilson Luiz Sanvito (Arquivos de Neuro-Psiquiatria)
ABSTRACT The Frenchman Gustave Flaubert, the Russian Fyodor Dostoevsky and the Brazilian Machado de Assis are known for their immeasurable contributions to literature. However, what most people do not know is that all three authors suffered from epilepsy and were affected by their neurological condition in different ways. We offer a short description of how epilepsy influenced their lives, how they dealt with it and how their neurological condition was present in their novels and correspondence. Their lives are excellent examples of how intimately neurology can be entwined in art and history, and provide an important perspective on patients with epilepsy.